(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Children are the nation’s most valuable asset in the future, monitoring and stimulation of growth and development is one way for children to achieve optimal growth and development. Every child needs to be stimulated and monitored regularly as early as possible appropriately and continuously, both in the family and at school. Monitoring growth and development is carried out to find out whether children grow and develop according to their age and stage of development and can detect deviations in child growth and development. The purpose of this community service is to increase knowledge and provide training to early childhood teachers regarding early detection of child growth and development. This community service method is to conduct counseling about growth and development and early detection, followed by training for early detection of growth and development. Community service results: Pretest results show that of the 35 early childhood teachers who participated in the activity, 13 teachers had poor knowledge, and 12 teachers had sufficient knowledge, and 10 teachers had good knowledge. The results of the posttest after the counseling were 35 early childhood teachers who had good knowledge. The conclusion of community service is: There is an increase in knowledge after counseling on growth and development and early detection.